Famesick : a memoir - Dunham, Lena, 1986- (Random House, 2026)
For the last decade, as she's spent countless hours in doctor's waiting rooms searching for diagnoses, treatments, and relief, being the owner and operator of Lena Dunham's body has felt, as she puts it, "like towing a wrecked car across town at midnight." It's not easy dragging a wrecked car anywhere, much less to the Met Gala while sewn into a gold lamé corset. Or to the set of the hit show that you -- as a twenty-five-year-old -- are writing, directing, producing, and starring in. Or to the White House, the Golden Globes, or your publicist's office to discuss the latest internet disaster. But Dunham does it -- even if it means interminable hospital stays, vomiting in the bathroom when she's meant to be meeting Oprah, or terrifying those closest to her -- because she can no longer tell the difference between fighting to do what she loves and being a servant to her own ambition. All the while, she is holding out for a love that can withstand her personal and public challenges and, more than anything, yearning to feel like herself again -- if only she could remember who that self was. As Dunham takes us through her journey, tracking her rise to fame -- from selling the pilot of Girls to the present -- in three acts, it becomes clear that the spotlight casts long shadows, distorting the relationships she once held dear and isolating everyone in its glare. When an endless supply of drugs can't protect you from pain -- and begins to control your every move -- being famous doesn't stand a chance against the darker corners of the human experience. In Famesick, Dunham asks herself what the cost of fulfilling her dreams has really been, and whether it was worth it. What she finds is deeper than physical relief, and more lasting, as she learns to live with what she can't change and turn her regrets into wisdom that can carry her forward, as she reconnects to what, and who, she loves.